Kyrgyz Republic : 2019 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2019)
The economy is growing steadily, benefiting from a benign regional environment, particularly in Russia, the source of most remittances and non-gold export receipts. Low inflation, lower fiscal deficits, and a stable banking sector point to the success of stabilization policies implemented by the government and National Bank of the Kyrgyz Republic (NBKR, the central bank) under eight successive Fund-supported programs. However, the economy remains vulnerable to external shocks because of the high level of remittances (29 percent of GDP), the concentration of exports on gold (37 percent of exports of goods), the level and composition of the public debt (56 percent of GDP, 4/5 of which is denominated in foreign currency), and the level of the current account deficit (8.7 percent of GDP). In addition, economic growth has been insufficient to significantly raise living standards and continue to reduce poverty.